2021
DOI: 10.21203/rs.3.rs-763583/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of Noni on memory impairment induced by hydrocortisone in mice

Abstract: Background Oxidative stress and memory impairment have been implicated, a common functional brain disease. Nuclear factor E2-related factor 2 (Nrf2) is highly induced in oxidative stress, indicating that Nrf2 is an emerging target of memory therapy. This study aimed to investigate the effect of Noni on brain memory impairment induced by hydrocortisone and its protection mechanism in mice. Methods Male Kuming mice were (n = 8/group) given hydrocortisone by gastric gavage for 14 consecutive days to establish t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Based on these findings, it can be suggested that noni might be a powerful antioxidant and protect nerve cells. Noni may possess a potential benefit for the treatment of memory impairment [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on these findings, it can be suggested that noni might be a powerful antioxidant and protect nerve cells. Noni may possess a potential benefit for the treatment of memory impairment [ 40 ].…”
Section: Discussionmentioning
confidence: 99%